Physiological and Proteomic Signatures Reveal Mechanisms of Superior Drought Resilience in Pearl Millet Compared to Wheat - Ghatak, Arindam; Chaturvedi, Palak; Bachmann, Gert; Valledor, Luis; Ramšak, Živa; Bazargani, Mitra Mohammadi; Bajaj, Prasad; Jegadeesan, Sridharan; Li, Weimin; Sun, Xiaoliang; Gruden, Kristina; Varshney, Rajeev K.; et al. (Frontiers in Plant Science, 2021)
Presently, pearl millet and wheat are belonging to highly important cereal crops. Pearl millet, however, is an under-utilised crop, despite its superior resilience to drought and heat stress in contrast to wheat. To investigate this in more detail, we performed comparative physiological screening and large scale proteomics of drought stress responses in drought tolerant and susceptible genotypes of pearl millet and wheat. These chosen genotypes are widely used in breeding and farming practices. The physiological responses demonstrated large differences in the regulation of root morphology and photosynthetic machinery revealing a stay green phenotype in pearl millet. Subsequent tissue-specific proteome analysis of leaves, roots and seeds led to the identification of 12,558 proteins in pearl millet and wheat under well-watered and stress conditions. To allow for this comparative proteome analysis and to provide a platform for future functional proteomics studies we performed systematic phylogenetic analysis of all orthologues in pearl millet, wheat, foxtail millet, sorghum, barley, brachypodium, rice, maize, arabidopsis and soybean. In summary, we define (i) a stay green proteome signature in the drought tolerant pearl millet phenotype and (ii) differential senescence proteome signatures in contrasting wheat phenotypes not capable to cope with similar drought stress. These different responses have a major effect on yield and grain filling processes reflected by the harvest index. Proteome signatures related to root morphology and seed yield demonstrated the unexpected intra- and interspecies-specific biochemical plasticity for stress adaptation for both pearl millet and wheat genotypes. These quantitative reference data provide tissue- and phenotype-specific marker proteins of stress defense mechanisms which are not predictable from the genome sequence itself and have potential value for marker-assisted breeding beyond genome assisted breeding.